Elemental composition of organic aerosol: The gap between ambient and laboratory measurements. Issue 10 (22nd May 2015) - Chen, Qi; Heald, Colette L.; Jimenez, Jose L.; Canagaratna, Manjula R.; Zhang, Qi; He, Ling‐Yan; Huang, Xiao‐Feng; Campuzano‐Jost, Pedro; Palm, Brett B.; Poulain, Laurent; Kuwata, Mikinori; Martin, Scot T.; et al.
Abstract A large data set including surface, aircraft, and laboratory observations of the atomic oxygen‐to‐carbon (O:C) and hydrogen‐to‐carbon (H:C) ratios of organic aerosol (OA) is synthesized and corrected using a recently reported method. The whole data set indicates a wide range of OA oxidation and a trajectory in the Van Krevelen diagram, characterized by a slope of −0.6, with variation across campaigns. We show that laboratory OA including both source and aged types explains some of the key differences in OA observed across different environments. However, the laboratory data typically fall below the mean line defined by ambient observations, and little laboratory data extend to the highest O:C ratios commonly observed in remote conditions. OA having both high O:C and high H:C are required to bridge the gaps. Aqueous‐phase oxidation may produce such OA, but experiments under realistic ambient conditions are needed to constrain the relative importance of this pathway.